Pancreatology : A Clinical Casebook - Gardner, Timothy B.; Smith, Kerrington D. (Springer International Publishing : Imprint: Springer, 2017)
This clinical casebook provides a comprehensive yet concise state-of-the-art review of pancreatic disease. Presented in a case-based format, each case focuses on a different varient of pancreatic disease and pancreatic cancer, with sections on diagnosis and early detection, management of the disease, and treatment of complications from the disease. The role of neoadjuvant therapy for pancreatic cancer and emerging treatment algorithms for chronic pancreatitis are also highlighted in the text. Written by experts in the field, Pancreatology: A Clinical Casebook is a valuable resource for clinicians, surgeons, and researchers interested in caring for patients with pancreatic disease. .